2016
DOI: 10.1073/pnas.1605737113
|View full text |Cite
|
Sign up to set email alerts
|

Hair cells use active zones with different voltage dependence of Ca 2+ influx to decompose sounds into complementary neural codes

Abstract: For sounds of a given frequency, spiral ganglion neurons (SGNs) with different thresholds and dynamic ranges collectively encode the wide range of audible sound pressures. Heterogeneity of synapses between inner hair cells (IHCs) and SGNs is an attractive candidate mechanism for generating complementary neural codes covering the entire dynamic range. Here, we quantified active zone (AZ) properties as a function of AZ position within mouse IHCs by combining patch clamp and imaging of presynaptic Ca 2+ influx an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
277
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(310 citation statements)
references
References 71 publications
(115 reference statements)
29
277
4
Order By: Relevance
“…Recent work in mouse IHCs found that, compared with smaller ribbons, Ca V 1.3 channels at larger ribbons within the same hair cell were activated at more depolarized membrane potentials creating a higher threshold for activation (Ohn et al, 2016). By contrast, we saw a similar activation of the calcium current in transgenic hair cells compared with WT hair cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in mouse IHCs found that, compared with smaller ribbons, Ca V 1.3 channels at larger ribbons within the same hair cell were activated at more depolarized membrane potentials creating a higher threshold for activation (Ohn et al, 2016). By contrast, we saw a similar activation of the calcium current in transgenic hair cells compared with WT hair cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IHC Ca V 1.3 Ca 2+ channels stand out by reason of their hyperpolarized activation range and modest inactivation (10,18,19,22,45). These properties have been attributed to the molecular composition of the native Ca 2+ -channel complexes that, in addition to the specific pore-forming Ca V 1.3α1 splice variant (46), auxiliary Ca V β2 (6,47), and Ca V α 2 δ2 (7) subunit, also contain interactions partners, such as Rab3-interacting molecule (RIM) (48,49); harmonin (50, 51); calmodulin; and, notably, CaBPs (this study and refs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were differences in the size of the synaptic ribbon, with the ribbons on modiolar side being larger and more elongated; however, the significance of this observation is obscure. Other work has suggested a presynaptic variation such that Cav1.3 Ca 2+ channels on the pillar side may activate at more hyperpolarized potentials than those on the modiolar side, thereby allowing Ca 2+ entry for weaker depolarization (217). At this stage, the origin of the heterogeneity in synaptic sensitivities and related spontaneous activities is not fully understood.…”
Section: Signal Transmissionmentioning
confidence: 99%